FABRICATION AND CONTACTING INDIVIDUAL GOLD NANOWIRES - Karim, S.; Ensinger, W. (The Nucleus, 2020)
Gold nanowires with diameters ranging from 80 to 320 nm are electrochemically fabricated in etched single-pore membranes. By means of two macroscopic planar electrodes on either side of the membrane, single nanowires are successfully contacted. The fabrication and contacting method is presented and the measured resistance-versusdiameter behavior of the nanowires is discussed, considering electron scattering both at the wire surface and at the grain boundaries.